INTERVENTION OF NOVEL TEACHING TECHNIQUES AND PRACTICES - Chowdhury, Suvashree Roy (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The prime target of this article is to shed light on the various innovative and novel teaching practices that targets to enhance the teaching-learning process. Pedagogy which in a layman’s language connotes to the art and science of teaching has various other implicit as well as explicit expressions to it. Of late, teaching and learning procedures have undergone sea changes. Education system has become more technology based. Good amount of stress is now being vested in creative thinking and education has a more interdisciplinary as well as multidisciplinary approach. Enormous resources are being now put into upgrade and revamp the education system. This a is a worldwide phenomenon. This article mainly focuses on certain innovative practices that are now being implemented to improve the teaching standards and help students reach their proper learning outcome through proper understanding. Techniques such as – Experiential learning; Inquiry based learning; Embodied education system; Stealth Valuation technique, Argumentation technique; Behavioural Management practices and various other pedagogical processes constitutes this article. Nevertheless, the pros and cons of such techniques is also discussed.